The effectiveness of using participatory evaluation in enhancing institutional performance: a case study from the United Arab Emirates - Elhakim, Ahmed (Frontiers in Education, 2025)
IntroductionParticipatory evaluation has gained attention as a collaborative approach to institutional assessment, promoting shared decision-making and stakeholder engagement. However, its effectiveness within higher education, particularly in the Gulf region, remains underexplored. This study aims to examine how a participatory evaluation process influences institutional performance and stakeholder engagement in a higher education institute in the United Arab Emirates.MethodsA qualitative case study approach was adopted, using document review, an evaluation scale, and semi-structured interviews with 17 stakeholders. This multi-method design enabled triangulation of institutional data and stakeholder perspectives, strengthening the credibility and depth of the findings. The approach was chosen to provide a comprehensive understanding of both measurable institutional changes and the experiences of those involved in the participatory evaluation process.Results and discussionThe findings indicate strengthened quality assurance systems, enhancements in academic programs, and increased stakeholder engagement. Participants reported a greater sense of empowerment, improved collaboration, and capacity building, though stakeholder diversity was moderate and involvement of non-evaluators partial. Conceptually, the study situates participatory evaluation within institutional quality assurance frameworks, challenging traditional top-down models. Practically, it offers higher education institutions in similar contexts a structured approach to fostering inclusive decision-making and sustainable institutional self-improvement.